ANALISIS PENGARUH CORPORATE GOVERNANCE TERHADAP HUBUNGAN INVESTMENT OPPORTUNITY SET DAN NILAI PERUSAHAAN PADA PERUSAHAAN INDUSTRI MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA - Lauraincia Van Houten (Jurnal Cita Ekonomika, 2019)
This study aims to examine the effect of corporate governance negative investment opportunity set (IOS) on firm value. By using a sample of 235 samples obtained from 47 manufacturing companies listed on the Indonesia stock exchange during the 2009-2013 observation period, this study proves that the investment opportunity set (IOS) has a positive and significant effect on firm value (hypothesis 1 is rejected); the supervisory function carried out by independent commissioners is able to reduce the opportunistic behavior of managers in making investments (hypothesis 2 is accepted); there is a positive and significant value for the interaction coefficient of investment opportunity set (IOS) with institutional ownership (hypothesis 3 is accepted). This means that large institutional ownership in the company will have a good influence on management in allocating funds that are trusted by investors; coefficient of interaction of investment opportunity set (IOS) with managerial ownership is positive but not significant (hypothesis 4 is rejected). Managerial ownership does not have a significant effect on increasing company value. The coefficient of determination of the results of this test is 0.589, this means that the investment opportunity set (IOS), Independent Commissioner, Institutional Ownership, Managerial Ownership are able to explain the Corporate Value of 58.9%. In other words, other factors outside of this research model that influence the Company Value by 41.1%.